2016
DOI: 10.5020/18061230.2016.p342
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em pessoas com leishmaniose cutânea

Abstract: Calidad de vida de personas con leishmaniasis cutánea RESUMOObjetivo: Avaliar a qualidade de vida (QV) de pessoas com leishmaniose cutânea. Métodos: Estudo observacional transversal e descritivo realizado em Brasília, DF, Brasil em 2013 com 44 pacientes portadores de leishmaniose cutânea, por meio da aplicação de um questionário sociodemográfico e clínico e do WHOQOL-bref. Os dados sofreram análises descritivas de frequência, tendência central e dispersão e análise inferencial de comparação entre domínios. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Given that patients with CL mostly reside away from health facilities and/or in rural locations, it is plausible to infer that their diagnosis and treatment incurred a substantial indirect financial burden, which may have compromised their limited family budgets 31 .The additional costs incurred by the patients were also associated with a negative perception of CL. Similarly, a study carried out with patients treated at a referral center in the Brazilian state of Minas Gerais found that disease-related expenses above US$ 137 significantly impacted the patient's quality of life 31 . The authors also demonstrated that dissatisfaction with financial resources among individuals treated for CL negatively impacted their quality of life 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that patients with CL mostly reside away from health facilities and/or in rural locations, it is plausible to infer that their diagnosis and treatment incurred a substantial indirect financial burden, which may have compromised their limited family budgets 31 .The additional costs incurred by the patients were also associated with a negative perception of CL. Similarly, a study carried out with patients treated at a referral center in the Brazilian state of Minas Gerais found that disease-related expenses above US$ 137 significantly impacted the patient's quality of life 31 . The authors also demonstrated that dissatisfaction with financial resources among individuals treated for CL negatively impacted their quality of life 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Apesar dos sucessivos treinamentos e capacitações ofertadas aos profissionais da rede básica de saúde que estão envolvidos nos cuidados destes pacientes, é provável que o enfoque às condições psíquicas e emocionais que o indivíduo possa apresentar sejam subestimadas no percurso da doença e no tratamento. Para alguns autores isso poderia ser decorrente do fato da doença não ameaçar diretamente a vida 5 . Neste paciente observou-se a repercussão do agravo no psiquismo que provocou uma imagem corporal negativa, reduziu a autoconfiança, interferiu nas suas relações sociais e resultou na dificuldade de adesão ao tratamento.…”
Section: Discussionunclassified